Computational Assessment of Groundwater Potential of the Teluk Datuk – Olak Lempit Aquifer - Mohamed Zawawi, Mohamed Azwan (2000)
Malaysia is endowed with abundant surface water resources. However, the distribution of the rainfall in time and space has resulted in limited availability of water of acceptable quantity and quality for domestic water use in some parts of the country. The purpose of this study was to determine areas of groundwater potential and to assess the amount of potentially available groundwater and its quality. It was envisioned that with the proposed development of the groundwater resource in the area, the available surface water and the additional groundwater would meet the domestic need of the people in the area. Several pumping tests were carried out by Geological Survey Department and Rintisan Sdn. Bhd. at Teluk Datuk - Olak Lempit aquifer. Results of the tests showed that the formation was proven to yield water of considerable quantity. THWells software was used to calculate the drawdown due to the combined effect of 2 and 4 discharge wells. The results showed that the drawdown could be as high as 18 m if pumping was carried out once a year at 5 MGD pumping rate. The drawdown would cause water from a river nearby to flow into the aquifer but would not affect the quality of well water. From the results of groundwater quality test, there were two parameters which were higher than the standards. The parameters were Ammonia Nitrogen and Chemical Oxygen Demand. The maximum length of saltwater intrusion was 1.185km when the nearest wellfield was about 14 to 15 km from the sea. This means the groundwater quality was not affected by the salt- water intrusion. A three-dimensional finite-difference groundwater flow code known as MODFLOW was used in this study. From the analysis, it could be deduced that the suitable rate of pumping for the study area was 25.5 MGD, which did not affect the surroundings including the Paya Indah wetland. If there was no recharge at all for the whole year, then the suitable rate of pumping was around 10 to 12 MGD only. With the development of this groundwater project, some of the water supply problems in the Klang Valley can be alleviated. The Teluk Datuk - Olak Lempit aquifer can be developed as a reliable alternative source of water supply.